Combined Open and Endoscopic Endonasal Skull Base Resection of a Rare Endometrial Carcinoma Metastasis - Stamates, Melissa M.; Lee, John M.; Merrell, Ryan T.; Shinners, Michael J.; Wong, Ricky H. (Journal of Neurological Surgery Reports, 2018)
In the absence of significant extracranial disease, patients with solitary brain metastases have shown benefit with resection. Brain lesions due to endometrial cancer are uncommon, and the only described skull base involvement is limited to the pituitary gland. We report the case of a 60-year-old female with endometrial cancer who presented with weeks of right cheek pain and numbness that was accompanied by headaches. We describe the magnetic resonance imaging (MRI) findings and surgical resection of a solitary endometrial metastasis involving the infratemporal fossa, middle fossa, cavernous sinus, trigeminal nerve, and nasal sinuses. Due to extensive nasal and lateral involvement, a combined open and endoscopic approach was planned. The patient was discharged home without complication. She underwent adjuvant radiotherapy. Despite its suspected indolent course, intracranial endometrial adenocarcinoma metastases are gaining higher prevalence. This case report documents the first direct neural spread of an endometrial primary, and highlights the potential for extra-axial sites of metastasis.
Keywords: skull base metastasis; endometrial carcinoma; endoscopic endonasal approach; neuro-oncology; anatomic pathology; middle fossa lesion